While Urine and Plasma Decorin Remain Unchanged in Prostate Cancer, Prostatic Tissue Decorin Has a Prognostic Value - Razie Rezaie; Zeinab Falakian; Saeideh Mazloomzadeh; Mohsen Ayati; Arman Morakabati; Mohammad Reza Teimouri Dastjerdan; Mohammad Zare; Minoosh Moghimi; Tina Shahani; Alireza Biglari (Iranian Biomedical Journal, 2020)
Background: Numerous studies confirmed that significant decrease in tissue decorin (DCN) expression is associated to tumor progression and metastasis in certain types of cancer including prostate cancer (PC). However, the potential prognostic value of tissue DCN in PC has not yet been investigated. Methods: A total number of 40 PC and 42 patients with benign prostatic hyperplasia (BPH) were investigated for the expression levels of DCN in their prostatic tissues using real-time quantitative polymerase chain reaction and immunohistochemical analyses. Urinary and plasma DCN levels were also measured by ELISA. Results: Despite no significant changes in the mean of urine and plasma DCN concentrations between the two study groups, tissue DCN mRNA was found to be 5.5fold lower in cancer than BPH (p = 0.0001). Similarly, the stained DCN levels appeared significantly lower in cancer patients with higher Gleason Scores (8 and 9, n = 6) than those with lower Gleason Scores (6 and 7, n = 26), with a p value of 0.049. Conclusion: Here, we report, for the first time, that urine and plasma DCN does not seem to have a diagnostic value in PC, while tissue DCN could potentially be used as a prognostic marker in PC.